Nitrate-Rich Fruit and Vegetable Supplement Reduces Blood Pressure in Normotensive Healthy Young Males without Significantly Altering Flow-Mediated Vasodilation: A Randomized, Double-Blinded, Controlled Trial - Karen L. Sweazea; Carol S. Johnston; Brendan Miller; Eric Gumpricht (Journal of Nutrition and Metabolism)
Nitric oxide (NO) is a primary vasodilatory factor released from endothelial cells of the peripheral vasculature. NO production is stimulated through enzymatic-dependent mechanisms via NO synthase and from dietary intake of nitrate-containing foods or supplements. We evaluated the efficacy of a nitrate-rich fruit and vegetable liquid supplement (FVS, AMPED NOx, Isagenix International LLC) versus a juice low in nitrates (prune juice, PRU) on circulating nitrates/nitrites as well as cardiovascular parameters in 45 healthy normotensive men (18–40 y). Blood pressure, flow-mediated dilation (FMD), and plasma nitrates and nitrites were measured at baseline and after two weeks of supplementation (2 oz/d). Subjects also completed questionnaires on sleep quality and mood since these measures have been associated with endothelial function. In contrast to PRU, FVS significantly increased plasma nitrates and nitrites (+67%, p<0.001) and decreased diastolic blood pressure (−9%, p=0.029) after two weeks. The change in FMD for FVS supplementation versus PRU supplementation was not significant (+2% vs. −9%, respectively, p=0.145). Changes in sleep quality or total mood state did not differ between groups after the 2-week study. Thus, the nitrate-rich FVS supplement increased plasma NO and reduced diastolic blood pressure in young normotensive men, but increased plasma NO was not associated with improvements in FMD, mood, or sleep. This trial is registered with ClinicalTrials.gov NCT03486145.